Abstract Art as an Inspiration to Create Textile Patterns through Computer Aided Designing - Zunaira Jamil; Mehreen Ijaz (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Art breaks away from the traditional representation of everyday objects and familiar subjects. The viewer is not distracted by meaningful images, so the mind is stirred into felling the energy and spirit of a design. Art does not reflect any form of realism, in fact, it breaks the rules. This study aimed at creating unique patterns for textiles through computer-aided design by taking abstract art as a source of inspiration. It was completed in three phases. First phase comprised of a selection of various inspirational themes from Abstract Art. In the second phase, an experimental approach was taken by developing various patterns through a range of colours and layouts to discover the best and most suitable for the end products. The created patterns were then applied to each category of apparel as 2D and 3D models through Adobe Illustrator and Adobe Photoshop. In the third phase, an online survey was conducted to investigate the market demand of consumers towards developed designs. The results showed that 60% respondents strongly appreciated the uniqueness of design, 56% respondents liked the colour scheme, and 62% of respondents preferred to have this design in their wardrobe. 57% respondents were strongly agreed that the principles of design were well balanced. It was concluded that Marbling Abstract art becoming more popular pattern for apparel due to its bright colour shades, different lines and triangle shapes which attract the participants. The study will be beneficial for the textile designers to opt for multiple categories from abstract art for developing patterns in apparel.